BS EN IEC 61755-2-2. Fibre optic interconnecting devices and passive components. Connector optical interfaces. Part 2-2. Connection parameters of dispersion unshifted single-mode physically contacting fibres. Angled (17th July 2020) - British Standards Institution,
No abstract available